Exercise ameliorates hepatic lipid accumulation via upregulating serum PRL and activating hepatic PRLR-mediated JAK2/STAT5 signaling pathway in NAFLD mice - Fan, Jia; Nie, Kaidi; Liu, Xiaobing; Liu, Jiao; Shao, Binghua (Frontiers in Pharmacology, 2025)
ObjectiveNon alcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases, closely related to overnutrition, obesity, and metabolic syndrome. This study used exercise intervention on NAFLD mice to investigate the effect of aerobic exercise on NAFLD.MethodAfter one week of acclimatization, the mice were randomly divided into two groups: a control group (C group, n = 14) fed a standard diet and a model group (M group, n = 24) fed a high-fat diet. At the end of the 10th week, four mice from each group were randomly selected for liver pathological sectioning and Oil Red O staining to assess hepatic lipid droplet formation and confirm the successful establishment of the NAFLD model. Subsequently, the remaining mice in M group were further randomized into two subgroups: a model control group (CM group, n = 10) and a model exercise group (EM group, n = 10). After modeling, the blood glucose tolerance of mice, HE staining and red oil staining of liver tissue, HDL-C, LDL, TC, TG, AST, ALT, PRL content in serum, and JAK, PRLR, STAT5 content in liver were detected.ResultThe glucose tolerance test found that at 10 and 30 minutes, compared with the C group, the blood glucose level in the CM group increased (P < 0.05), while the blood glucose level in the EM group decreased compared to the CM group (P < 0.05); After 60 minutes, there was no statistically significant difference in blood glucose levels among the groups of rats compared to C group, the final body weight of CM group and EM group was significantly higher (P < 0.01). The final body weight of EM group was significantly lower than that of CM group (P < 0.01). In terms of liver index, both C group and EM group showed significantly lower values than CM group (P < 0.01). Compared to C group, both CM group and EM group exhibited significantly higher levels of TC and LDL-C (P < 0.01) whereas HDL-C levels were significantly lower in CM group (P < 0.01). When compared to CM group, EM group showed significantly reduced LDL-C levels (P < 0.01), while HDL-C levels were significantly higher (P < 0.01). Compared with group C, there were significant differences in serum AST, ALT, and PRL levels in the CM group (P < 0.01). There were significant differences in serum AST, ALT, and PRL levels between the EM group and the CM group (P < 0.05).The gene testing results of JAK and STAT5a showed no statistical difference in expression among the three groups. The PRLR gene results showed that compared with the C group, the PRLR in the CM group was significantly reduced (p < 0.01); Compared with the CM group, the PRLR in the CE group was significantly increased (p < 0.01). Compared with group C, the expression levels of PRLR and p-STAT5 were significantly reduced in both CM and EM groups (p < 0.01). The p-JAK2 levels in the CM group were significantly reduced compared to the C group (p < 0.01). The expression levels of PRLR, p-JAK2, and p-STAT5 in the EM group were significantly higher than those in the CM group (p < 0.01).ConclusionExercise may moderately elevate serum prolactin (PRL) levels, thereby reducing intrahepatic lipid accumulation and ameliorating non-alcoholic fatty liver disease (NAFLD). The underlying mechanism may involve upregulation of the hepatic classical PRLR-mediated JAK2/STAT5 signaling pathway.